Liquidity shocks and their effects on entrepreneurship - Torello, Eugenia Josefina Fernandez (2015)
The objective of this study is to analyze how liquidity shocks affect households\' decisions related to entrepreneurial activities in order to identify whether households are liquidity constrained. This study focused on households\' responses to anticipated income shocks, via the receipt of pension benefits, since under complete markets, decisions should not be affected by a liquidity shock when the timing and amount of that shock are known. We exploited the fact that eligibility rules for old age pension were partially determined by age and used a Fuzzy Regression Discontinuity Design to estimate the causal effects. The results suggest that Brazilian small business owners in the informal sector of the economy are liquidity constrained.